How did local wisdom and practice make schools thrive during the pandemic? Evidence from a positive deviance study in rural Uganda - Atuhurra, Julius; Kim-Hines, Yoonjung; Nishimura, Mikiko (Emerald, 2023)
Purpose This research explores the impact of the locally grown strategies for learning support, as a positive deviance (PD) study, during the COVID-19 pandemic in rural Uganda. Design/methodology/approach The researchers employed a randomized control trial (RCT) as an original design whereby 50 schools received a full package of SMS and WhatsApp peer groups of head teachers, 50 schools received SMS only and another 50 served as a control group. As an analytical method, this study adopted a difference-in-difference (DID) model to analyze the impact of the radio talk shows promoted through SMS followed by discussion among WhatsApp peer groups. The data collected in June 2021 and February 2022 were used due to the COVID-19-related data limitation of the baseline survey collected in 2019. Findings The authors found that the local radio talk shows as a PD intervention had a humble impact on preventing pupils’ dropout during the school closures for two years in Uganda. However, the authors did not obtain a significant result on the impact of the PD intervention on pedagogical support or learning outcomes at the school level. The authors also found that the pupils have significantly dropped their level of proficiencies in literacy and numeracy during the pandemic. Originality/value The findings could be of value for the leaders, educators and policymakers to understand the most recent update of learning situation in Uganda and the potential impact of locally grown strategies for learning which does not require external inputs.